Adult Education in Sub-Saharan Africa - Lauglo, Jon (World Bank, Washington, DC, 2012)
The note describes the major findings of the study "Engaging with adults", which reviews the international experience with adult basic education (ABE), with a focus on Africa. As a foundation for improved conditions of life, basic education serves not only the young, but adolescents and adults who may have been missed by the educational system. Illiteracy is a major barrier to poverty alleviation, and needs to be addressed, through quality education, and effective ABE programs. The note outlines a range of policy issues for governments to strengthen its support of ABE, from targeting vulnerable groups, through the roles governments and nongovernmental organizations can play - including those of businesses and industry - to institutionalizing ABE, thus enhancing literacy and numeracy, as well as information technology. Recommendations suggest strong political leadership, and considerable investment in institutional development to diversify programs so as to be responsive to local demand.